Análisis a los estados financieros de la constructora Nexusterra s.a. en la ciudad de Santo Domingo, período 2014 - 2015 - Montero Tufiño, Aracely Anabel (2017)
The thesis work was done in compliance with the requirements prior to obtaining the degree of Accounting and Auditing Engineer, Public Accountant - Auditor CPA, at the National University of Loja, in accordance with the current Academic Regulations. The analysis of the Financial Statements of the Constructor was based on the fulfillment of the objectives set forth: a diagnosis of the economic and financial situation by means of the horizontal analysis to know the weaknesses and strengths of the entity for the periods subject to studies, Financial indicators were applied to determine the level of financial economic profitability in the two years analyzed, to compare the financial situation of the entity for the periods, and to suggest the results obtained by providing recommendations to the Manager of the Company based on the work performed, with the Purpose of improving the levels of profitability of the financial entity. With this proposal a report of the results obtained was given to the Manager of the Construction Company NEXUSTERRA SA, in which it is shown mainly that the Constructor has an acceptable economic and financial profitability during the analyzed period, improving its liquidity and taking advantage of the information to Making timely decisions when investing in construction projects. The following indices were applied: liquidity that allowed measuring its ability to meet short-term obligations as they expire. Indebtedness Index, allowed us to calculate how much is owed to the company and if it generates enough profit to pay the principal and interest. Efficiency Index, measured the speed with which several accounts are converted into sales or cash. Performance Index, I facilitate the assessment of the company's profits against a given level of sales.